2023
DOI: 10.1177/17475198231159051
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective lanthanide-doped ion sieves for lithium recovery from aqueous solutions

Abstract: The increased global demand for lithium is rapidly depleting the lithium ore reserves. Therefore, attention has turned to the recovery of lithium from aqueous solutions, such as lithium-containing brine. Compared with other methods of lithium recovery, adsorption is energy efficient and simple to implement, increasing demand for selective lithium adsorbents. In this study, a selective lithium-ion adsorbent, H4Ti5– xLa xO12, was synthesized via the sol–gel method, followed by heat treatment and acid washing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…The highest Li + adsorption potential was recorded at pH 10 for the SDS@Ag-CaO nanocomposites compared to PVP@Ag-CaO, which may be due to several reasons: (i) the anionic nature of SDS (anionic surfactant), whereas PVP is a non-ionic surfactant, and (ii) the presence of a very strong negatively charged sulfonate group in SDS, which is not present in the PVP surfactant [66]. Zheng et al [67] reported a similar type of pH effect trend by using the designed lanthanide-doped ion sieves. In that work, it was recorded that, by increasing the Li + solution pH from 2 to 10, the Li + adsorption potential of the ion sieve adsorbents also increased.…”
Section: Effect Of Ph On LI + Adsorption Performancementioning
confidence: 99%
“…The highest Li + adsorption potential was recorded at pH 10 for the SDS@Ag-CaO nanocomposites compared to PVP@Ag-CaO, which may be due to several reasons: (i) the anionic nature of SDS (anionic surfactant), whereas PVP is a non-ionic surfactant, and (ii) the presence of a very strong negatively charged sulfonate group in SDS, which is not present in the PVP surfactant [66]. Zheng et al [67] reported a similar type of pH effect trend by using the designed lanthanide-doped ion sieves. In that work, it was recorded that, by increasing the Li + solution pH from 2 to 10, the Li + adsorption potential of the ion sieve adsorbents also increased.…”
Section: Effect Of Ph On LI + Adsorption Performancementioning
confidence: 99%